'My best day will be my last day!': appreciating appreciative inquiry in police research. (3rd July 2022) - Skinns, Layla; Wooff, Andrew; Sprawson, Amy
ABSTRACT: Appreciative Inquiry is a methodology originating from organisational psychology, though it has since been used in criminal justice research including police studies. It is used to identify the actual and potential strengths of an individual or an institution, with a view to building on these strengths in the future. The primary purpose of this paper is to assess the value of Appreciative Inquiry for police research, where its use is potentially confounded by aspects of police culture. Drawing on an ESRC-funded study, the 'good' police custody study, we critically examine the role of Appreciative Inquiry in enabling access and data collection through appreciatively-informed interviews, examining this from the perspective of the police, the policed and police researchers. We also illustrate how Appreciative Inquiry contributed to the theorisation process and to the development of theoretically-informed recommendations and organisational reforms, matters that are neglected in other police and criminal justice research. We conclude that certain aspects of police culture hinder its use, for example, the cynicism of frontline police officers, whilst the storytelling features of police culture and growing collaboration between police and researchers help overcome these barriers. Appreciative Inquiry must still be used reflexively in police research, recognising for example the tendency towards naïve optimism and its impacts on vulnerable participants. Nonetheless, in light of Appreciative Inquiry dovetailing with growing expectations that the police and academics should work more closely together, there are grounds for appreciating Appreciative Inquiry as an important part of a diverse police research agenda in the future.